(untitled) - Quinn, Liam B. (New York, 1997)
Written by two Compaq engineers with extensive experience designing and building Fast Ethernet networks, this comprehensive guide gives the hands-on advice you need to quickly and efficiently migrate to a low-cost, reliable, high-speed networking environment and to optimize performance. The only Fast Ethernet guide written from the network manager's point of view, it emphasizes a complete understanding of the underlying technology as the key to implementation success. Several illustrated examples depict solid strategies for integrating Fast Ethernet technology into your network without incurring lengthy downtime or compromising current system capabilities.
Keywords: Ethernet (Hệ thống mạng cục bộ),Ethernet (Local area network system)